Policing cities: urban securitization and regulation in a twenty-first century world - Lippert, Randy (Routledge frontiers of criminal justice, 2013)
"Policing Cities brings together international scholars from numerous disciplines to examine urban policing, securitization, and regulation in nine countries and the conceptual issues these practices raise. Chapters cover many of the world's major cities, including New York, Beijing, Paris, London, Berlin, Mexico City, Johannesburg, Rio de Janeiro, Boston, Melbourne, and Toronto, as well as other urban areas in Britain, United States, South Africa, Germany, Australia and Georgia. The collection examines the activities and reforms of the traditional public police but also those of emerging public and private policing agents and spaces that fall outside the public police's purview and which previously have received little attention. It explores dramatic changes in public policing arrangements and strategies, exclusion of urban homeless people, new forms of urban surveillance and legal regulation, and securitization and militarization of urban spaces. The core argument in the volume is that cities are more than mere background for policing, securitization and regulation. Policing and the city are intimately intertwined. This collection also reveals commonalities in the empirical interests, methodological preferences, and theoretical concerns of scholars working in these various disciplines and breaks down barriers among them. This is the first collection on urban policing, regulation, and securitization with such a multi-disciplinary and international character. This collection will have a wide readership among upper level undergraduate and graduate level students in several disciplines and countries and can be used in geography/urban studies, legal and socio-legal studies, sociology, anthropology, political science, and criminology courses. "--